Early and middle latency auditory event-related potentials do not explain differences in neuropsychological performance between schizophrenia spectrum patients and matched healthy controls - Sahin, Derya; Hever, Felix; Bossert, Magdalena; Herwig, Kerstin; Aschenbrenner, Steffen; Weisbrod, Matthias; Sharma, Anuradha (Psychiatry research, 2021)
Abnormalities of early and middle latency auditory event-related potentials (ERPs) are widespread in schizophrenia and have been suggested to be associated with cognitive deficits in schizophrenia patients. In this cross-sectional study with schizophrenia patients (n=30) and psychiatrically healthy counterparts (n=31) (matched for age, sex, education), we investigated whether auditory information processing (measured via amplitudes and gating of the auditory ERPs P50, N100 and P200) correlates with neuropsychological performance across cognitive domains. The groups differed significantly in amplitudes and gating of N100 and P200 potentials as well as in neuropsychological performance, but not in P50 amplitude and gating. Neither amplitudes nor gating of auditory ERPs correlated with neuropsychological performance. Neuropsychological intergroup differences could not be explained by abnormalities in auditory information processing. Although pronounced impairments exist on the levels of both auditory information processing and cognitive performance in schizophrenia, these abnormalities are not directly associated with each other.